Clustering analysis and differentiation of lard from palm oil and soybean oil based on N-Alkane and Triacylglycerides profiles using chemometric analysis - Helmi Wasoh; Nur Ain Syaqirah Sapian; Ahmad Muhsin Mohammad Fatin; Murni Halim; Nor’Aini Abdul Rahman; Mohamad Zulfazli Mohd Sobri; Amalia Mohd Hashim; Mohd Termizi Yusof; Mohd Sabri PakDek; Yanty Noorzianna Abdul Manaf; Mohd Nasir Mohd Desa; Firdaus Mohamad Hamzah (hibiscus publisher, 2024)
This investigation focused on analyzing lard derived from pig adipose tissue and two different vegetable oils (crude palm oil and soybean oil) through triacylglycerides (TAGs) and n-alkane profiling, employing chemometrics techniques. Unsaponifiable palm and soybean oils were isolated and examined using gas chromatography-mass spectrometry (GC-MS) to assess their nalkane profiles. The identified n-alkane profiles were verified by comparing them with n-alkane standards (nC08–nC27). The experimental design incorporated several multivariate techniques, including Hierarchical Clustering Analysis (HCA), Principal Component Analysis (PCA), Random Forest (RF), and Partial Least Squares-Discriminant Analysis (PLS-DA). According to PLS-DA findings, nC25, nC27, and PPL are suggested as key TAG and n-alkane markers for the clustering analysis of lard from crude palm and soybean oils. These results indicate that further research is necessary to refine and validate these distinctions, especially when using chemometrics techniques.